1972
DOI: 10.1126/science.175.4023.753
|View full text |Cite
|
Sign up to set email alerts
|

Ultrathin Amorphous Coatings on Lunar Dust Grains

Abstract: UItrathin amorphous coatings have been observed by high-voltage electron microscopy on micrometer-sized dust grains from the Apollo 11, Apollo 12, Apollo 14, and Luna 16 missions. Calibration experiments show that these coatings result from an "ancient" implantation of solar wind ions in the grains. This phenomenon has interdisciplinary applications concerning the past activity of the sun, the lunar albedo, the ancient lunar atmosphere and magnetic field, the carbon content of lunar soils, and lunar dynamic pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
25
0
10

Year Published

1972
1972
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(37 citation statements)
references
References 15 publications
(10 reference statements)
2
25
0
10
Order By: Relevance
“…A distinctive microscopic feature of lunar soil grains was discovered soon after the return of the first Apollo samples, when high-voltage transmission electron microscope (HVTEM) observations showed that many soil grains were surrounded by thin amorphous rims (e.g., Dran et al, 1970;Bibring et al, 1972). These results, when combined with laboratory experiments on artificially irradiated grains, demonstrated that amorphous rims could form in response to the implantation of ions with solar wind energies.…”
Section: Introductionsupporting
confidence: 51%
“…A distinctive microscopic feature of lunar soil grains was discovered soon after the return of the first Apollo samples, when high-voltage transmission electron microscope (HVTEM) observations showed that many soil grains were surrounded by thin amorphous rims (e.g., Dran et al, 1970;Bibring et al, 1972). These results, when combined with laboratory experiments on artificially irradiated grains, demonstrated that amorphous rims could form in response to the implantation of ions with solar wind energies.…”
Section: Introductionsupporting
confidence: 51%
“…Early transmission electron microscope (TEM) observations revealed that regolith silicates have amorphous surface layers with thicknesses and microstructures similar to those found in experimentally irradiated analog materials (Dran et al, 1970;Bibring et al, 1972Bibring et al, , 1974Bibring et al, , 1975Borg et al, 1980Borg et al, , 1983. The chemical composition of the surface of natural regolith grains as determined by Auger, x-ray photoelectron, and secondary-ion spectroscopies was also seen as generally consistent with solar radiation effects (Yin et al, 1975a(Yin et al, , b, 1976Housley andGrant, 1975, 1976;Gold et al, 1975;Zinner et al, 1976).…”
Section: Introductionmentioning
confidence: 78%
“…The last mechanism above is based on measurements which show that radiant heating raises the top 1-2 cm of the lunar soil to 100-130°C for 5-7 d during the lunar daytime (Langseth et al, 1973;Mendell, 1976). Although such temperatures are relatively low, the duration of heating integrated over the estimated 5000-150,000 year surface residence time for small regolith grains (Duraud et aL, 1975;Borg et al, 1976) et al, 1970;Bibring et al, 1972Bibring et al, , 1974Bibring et al, , 1975Borg et al, 1980Borg et al, , 1983. The inner layer is not easily explained by heating effects alone, and solar ion radiation effects are therefore left as an alternative.…”
Section: Formation Of the Outer Rim Layermentioning
confidence: 99%
“…Until the recent return of the Hayabusa mission from S-type asteroid Itokawa , samplebased studies of space weathering focused exclusively on lunar soils returned from the Apollo missions and select asteroidal and lunar regolith breccia meteorites (Bibring et al 1972;Hapke et al 1975;McKay 1993, 1997;Bernatowicz et al 1994;Pieters et al 2000;Taylor et al 2001;Noble et al 2005Noble et al , 2011. These investigations indicated that space weathering features form as a product of two primary processes: (i) solar wind ion irradiation, which can cause partial or complete amorphization of material and possible chemical changes in grain rims, as well as erosion, transport, and redeposition of material on grain surfaces induced by ion sputtering, and (ii) micrometeorite impact events which promote melting, vaporization, and the recondensation of the target and impactor material.…”
Section: Introductionmentioning
confidence: 99%